2019
DOI: 10.1111/jsr.12868
|View full text |Cite
|
Sign up to set email alerts
|

External validation of a data‐driven algorithm for muscular activity identification during sleep

Abstract: Several automated methods for scoring periodic limb movements during sleep (PLMS) and rapid eye movement (REM) sleep without atonia (RSWA) have been proposed, but most of them were developed and validated on data recorded in the same clinic, thus they may be biased. This work aims to validate our data‐driven algorithm for muscular activity detection during sleep, originally developed based on data recorded and manually scored at the Danish Center for Sleep Medicine. The validation was carried out on a cohort o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Several studies have now shown that addition of upper-extremity electromyography significantly improves the sensitivity for RBD diagnosis; however, rare patients present with movements largely limited to the legs, highlighting the importance of evaluating multiple muscles for RSWA as well as a video review of PSG for abnormal behaviors [31,40]. More recently, automated and machine learning approaches for RSWA scoring have been published, which have shown promise for more time-efficient and standardized approaches for RBD diagnosis, although these approaches require further validation in large-scale multicenter studies [41,42]. Standardization of RSWA scoring and polysomnography recording practices to optimize RBD detection will be important for the accurate recruitment of patients and generalization of findings from therapeutic trials in RBD.…”
Section: Video Polysomnographymentioning
confidence: 99%
“…Several studies have now shown that addition of upper-extremity electromyography significantly improves the sensitivity for RBD diagnosis; however, rare patients present with movements largely limited to the legs, highlighting the importance of evaluating multiple muscles for RSWA as well as a video review of PSG for abnormal behaviors [31,40]. More recently, automated and machine learning approaches for RSWA scoring have been published, which have shown promise for more time-efficient and standardized approaches for RBD diagnosis, although these approaches require further validation in large-scale multicenter studies [41,42]. Standardization of RSWA scoring and polysomnography recording practices to optimize RBD detection will be important for the accurate recruitment of patients and generalization of findings from therapeutic trials in RBD.…”
Section: Video Polysomnographymentioning
confidence: 99%
“…Each participant was given a PLMS-index score which details the average number of limb movements per hour of sleep. Using the aforementioned techniques [15], [17], this study demonstrated an automated classification of participants with PLMD and RBD with an accuracy of 88.75% and 84.17%, respectively [16]. Once more this study was able to assess the performance of limb movement detection by achieving an automated PLMS-index score that correlated to the manual score by 84.99% and only had a slight bias towards over-predicting the PLMS-index [16].…”
Section: Related Workmentioning
confidence: 80%
“…As a result the concept of automated movement detection algorithm lends itself towards a non-parametric model that can incorporate numerous sensors and compensate for movement which can vary greatly in magnitude and severity. A handful of other studies demonstrate this through limb movement detection in participants with RBD and PLMD [15]- [17].…”
Section: Related Workmentioning
confidence: 86%
See 1 more Smart Citation
“…Future development of 3D video analysis in the context of RBD should aim at expanding the use of this technology in home settings without focusing on REM sleep only and without the need for manually selecting upper and lower body ROIs. Previous studies showing that people with iRBD have increased muscular activity also in NREM sleep [ 9 , 30 , 31 ] would support the hypothesis that identification of REM sleep might not be necessary, but further studies are needed to confirm this hypothesis. Furthermore, future studies should evaluate whether upper and lower ROIs can be automatically selected with segmentation [ 32 ] and pose estimation algorithms [ 33 ].…”
Section: Discussionmentioning
confidence: 96%